2021
DOI: 10.3390/molecules26061738
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cytotoxic Activity of Sanguinaria canadensis Extracts against Human Melanoma Cells and Comparison of Their Cytotoxicity with Cytotoxicity of Some Anticancer Drugs

Abstract: Melanoma is an enormous global health burden, and should be effectively addressed with better therapeutic strategies. Therefore, new therapeutic agents are needed for the management of this disease. The aim of this study was the investigation of cytotoxic activity of some isoquinoline alkaloid standards and extracts obtained from Sanguinaria canadensis—collected before, during, and after flowering—against three different human melanoma cells (A375, G361, SK-MEL-3). The cytotoxicity of these extracts was not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…S. canadensis has a long history of curing cancer in clinical use since the mid-19th century, and people have used a black salve derived from S. canadensis (Jellinek and Maloney, 2005; Lin et al, 2018 ) to cure skin cancer ( Croaker et al, 2016 ). Basic research also confirmed the possibility of its application in the treatment of human cancer through the in vivo experiments involving the S. canadensis extracts ( Tuzimski et al, 2021 ). The anticancer activity of sanguinarine, the main component of S. canadensis , against various human malignancies has been validated and reviewed ( Achkar et al, 2017 ).…”
Section: Plant Sources and Structural Features Of Chelerythrinementioning
confidence: 70%
See 2 more Smart Citations
“…S. canadensis has a long history of curing cancer in clinical use since the mid-19th century, and people have used a black salve derived from S. canadensis (Jellinek and Maloney, 2005; Lin et al, 2018 ) to cure skin cancer ( Croaker et al, 2016 ). Basic research also confirmed the possibility of its application in the treatment of human cancer through the in vivo experiments involving the S. canadensis extracts ( Tuzimski et al, 2021 ). The anticancer activity of sanguinarine, the main component of S. canadensis , against various human malignancies has been validated and reviewed ( Achkar et al, 2017 ).…”
Section: Plant Sources and Structural Features Of Chelerythrinementioning
confidence: 70%
“…R.Br., and Sanguinaria canadensis L.) and Rutaceae (e.g., Zanthoxylum asiaticum (L.) Appelhans, Groppo & J.Wen) ( Zhang et al, 2005 ; Malikova et al, 2006 ; Wang et al, 2013 ). Direct scientific studies have proven that the abovementioned four plants have antitumor medicinal values ( Iwasaki et al, 2010 ; Deljanin et al, 2016 ; Ali et al, 2020 ; Tuzimski et al, 2021 ) , and CHE, as the most representative active compound for these plants, has also undergone a large number of studies on anticancer activity in vitro and in vivo , so there is a clear link between the compound and the traditional uses and the effects of these plants ( Chmura et al, 2000 ). ( Figure 2 )…”
Section: Plant Sources and Structural Features Of Chelerythrinementioning
confidence: 99%
See 1 more Smart Citation
“…Standard cancer treatment includes surgery, chemotherapy, radiation therapy, and immunotherapy. However, to date, there is no effective strategy to treat melanoma in clinical practice due to the side effects of chemotherapy and the development of multidrug resistance Yang et al, 2018;Khalifa et al, 2019;Tuzimski et al, 2021). Therefore, it is necessary to find an efficient, effective drug with fewer side effects and toxicity to treat melanoma (Kim et al, 2018;Yang et al, 2018;Abdulridha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to find an efficient, effective drug with fewer side effects and toxicity to treat melanoma (Kim et al, 2018;Yang et al, 2018;Abdulridha et al, 2020). Several studies have revealed that the phytochemical content of natural products has an anticancer activity that is very safe, non-toxic, readily available, and cost-effective (Khan et al, 2019;Mistiogiani et al, 2021;Tuzimski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%